A Scoping Review of the Evidence Behind Cytochrome P450 2D6 Isoenzyme Inhibitor Classifications. Issue 1 (13th February 2020) - Cicali, Emily J.; Smith, D. Max; Duong, Benjamin Q.; Kovar, Lukas G.; Cavallari, Larisa H.; Johnson, Julie A.
Abstract : The US Food and Drug Administration (FDA) lists 22 medications as clinical inhibitors of cytochrome P450 2D6 isoenzyme, with classifications of strong, moderate, and weak. It is accepted that strong inhibitors result in nearly null enzymatic activity, but reduction caused by moderate and weak inhibitors is less well characterized. The objective was to identify if the classification of currently listed FDA moderate and weak inhibitors is supported by publicly available primary literature. We conducted a literature search and reviewed product labels for area under the plasma concentration‐time curve (AUC) fold‐changes caused by inhibitors in humans and identified 89 inhibitor–substrate pairs. Observed AUC fold‐change of the substrate was used to create an observed inhibitor classification per FDA‐defined AUC fold‐change thresholds. We then compared the observed inhibitor classification with the classification listed in the FDA Table of Inhibitors. We found 62% of the inhibitors within the pairs matched the listed FDA classification. We explored reasons for discordance and suggest modifications to the FDA table of clinical inhibitors for cimetidine, desvenlafaxine, and fluvoxamine.